Controlling the production of phytotoxin pyriculol in Pyricularia oryzae by aldehyde reductase. Issue 1 (7th January 2021) - Furuyama, Yuuki; Motoyama, Takayuki; Nogawa, Toshihiko; Hayashi, Toshiaki; Hirota, Hiroshi; Kiyota, Hiromasa; Kamakura, Takashi; Osada, Hiroyuki
Abstract: Pyricularia oryzae is one of the most devastating plant pathogens in the world. This fungus produces several secondary metabolites including the phytotoxin pyriculols, which are classified into 2 types: aldehyde form (pyriculol and pyriculariol) and alcohol form (dihydropyriculol and dihydropyriculariol). Although interconversion between the aldehyde form and alcohol form has been predicted, and the PYC10 gene for the oxidation of alcohol form to aldehyde is known, the gene responsible for the reduction of aldehyde to alcohol form is unknown. Furthermore, previous studies have predicted that alcohol analogs are biosynthesized via aldehyde analogs. Herein, we demonstrated that an aldo/keto reductase PYC7 is responsible for the reduction of aldehyde to alcohol congeners. The results indicate that aldehyde analogs are biosynthesized via alcohol analogs, contradicting the previous prediction. The results suggest that P. oryzae controls the amount of pyriculol analogs using two oxidoreductases, PYC7 and PYC10, thereby controlling the bioactivity of the phytotoxin. Graphical Abstract: